CORRELATION OF READING COMPREHENSION SKILL AND ABILITY TO SOLVE MATHEMATICS STORY QUESTIONS OF STUDENTS IN INDONESIA: A META-ANALYSIS - Mentari, Rafinda Putri; Tuanaya, Rugaya; Albrecht, Michael (IAIN Ambon, 2023)
Abstrak Kemampuan siswa dalam memahami teks bacaan berhubungan positif dengan peningkatan prestasi belajar mereka. Penelitian ini bertujuan untuk menilai dampak keterampilan membaca terhadap kemampuan siswa dalam menyelesaikan masalah matematika. Metode yang digunakan adalah studi meta-analisis, di mana kami melakukan analisis sistematis dan meta-analisis terhadap sejumlah penelitian yang menyelidiki hubungan antara pemahaman bacaan dan kemampuan dalam menyelesaikan pertanyaan cerita matematika. Data yang kami gunakan berasal dari berbagai sumber penelitian yang dipublikasikan dalam jurnal dan tersedia dalam database online Google Scholar.AbstractThe ability of students to comprehend reading materials is indicative of a correlation, wherein the better students are at comprehending readings, the higher their learning achievement is likely to be. This research aims to examine the influence of reading skills on students' mathematical problem-solving abilities. This study employs a meta-analytical approach, conducting a systematic review and meta-analysis of various studies addressing the independent variable, which is the relationship between reading comprehension skills and the ability to solve mathematical word problems. The research data used are sourced from various research publications published in journals and uploaded to the online database Google Scholar.